Akibat Hukum Dilibatkannya Penduduk Sipil Dalam Konflik Bersenjata Antara Milisi Dan Tentara Pemerintah - Ervin Septory; Johanis Steny Franco Peilouw; Richard Marsilio Waas (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The relationship between people or groups of people incorporated in a different nationality or state of the community can be an indirect or official relationship undertaken by state officials that hold negotiations on behalf of the state and inaugurated the approval achieved in such an official inter-state agreement.Purposes of the Research: to know and understand the legal consequences of the civilian population involvement in armed conflict between militias and government soldiers.Methods of the Research: Based on the problems studied, this researcher uses a type of